Meta Analysis of The Influence of Problem Based Learning Models in High School Physics Students on Student Learning Outcomes - Arjuna Nora; - Asrizal (PILLAR OF PHYSICS EDUCATION, 2020)
The purpose of this research was to determine the effect size of the use of problem-based learning models in five categories, namely class level, material, aspects of knowledge, aspect of critical thinking skills, and aspects of problem solving skills. The method used in this research is meta-analysis. Data analyzed is secondary data obtained from the previous research. The sample of this research consists of 18 national articles and 2 international articles . The instrument used is the category code and the calculation of the size of the effect. Data analysis techniques in this study using the calculated effect size of each article. The results showed that the influence of the use of problem based learning model on the level of class X with the average of 1.22 in a category very high. Although, on the level of class XI with an average of 1,95 in the category of very high. Second, the influence of problem-based learning on the electric dynamic, motion, heat and temperature, and optical geometric was high. Moreover, Newton's Law is very high. Third, the influence of the problem-based learning model, on aspects of knowledge in the category of very high, aspects of critical thinking skills including high category, and aspects of skills problem solving belongs to the category of high